What Works and What Does Not: A Discussion of Popular Approaches for the Abandonment of Female Genital Mutilation - R. Elise B. Johansen; Nafissatou J. Diop; Glenn Laverack; Els Leye (Obstetrics and Gynecology International)
The prevalence of Female Genital Mutilation (FGM) is reducing in almost all countries in which it is a traditional practice. There are huge variations between countries and communities though, ranging from no change at all to countries and communities where the practice has been more than halved from one generation to the next. Various interventions implemented over the last 30–40 years are believed to have been instrumental in stimulating this reduction, even though in most cases the decrease in prevalence has been slow. This raises questions about the efficacy of interventions to eliminate FGM and an urgent need to channel the limited resources available, where it can make the most difference in the abandonment of FGM. This paper is intended to contribute to the design of more effective interventions by assessing existing knowledge of what works and what does not and discusses some of the most common approaches that have been evaluated: health risk approaches, conversion of excisers, training of health professionals as change agents, alternative rituals, community-led approaches, public statements, and legal measures.